Testing part of a DSGE model by indirect inference - Patrick Minford; Michael R. Wickens; Yongdeng Xu (Cardiff University, Cardiff Business School, 2016)
We propose a new type of test. Its aim is to test subsets of the structural equations of a DSGE model. The test draws on the statistical inference for limited information models and the use of indirect inference to test DSGE models. Using Monte Carlo experiments on two subsets of equations of the Smets-Wouters model we show that the model has accurate size and good power in small samples. In a test of the Smets-Wouters model on US Great Moderation data we reject the specification of the wage-price but not the expenditure sector, pointing to the first as the source of overall model rejection.
Keywords: C12; C32; C52; E1; 330; sub sectors of models; limited information; indirect inference; testing DSGE models equations; Monte Carlo; power; test size